Analysis of swamp irrigation water quality for agricultural areas: Case study DIR Polder Kaludan, Hulu Sungai Utara Regency - Muhamad Nuryanto; Mahmud Mahmud (CV. Literasi Indonesia, 2026)
The Kaludan Polder Swamp Irrigation Area (DIR) plays a crucial role in supporting swamp farming and controlling flooding in the Hulu Sungai Utara Regency. However, activities in the upstream and surrounding areas of the polder have the potential to degrade the quality of water entering the irrigation system. Therefore, water quality evaluation is necessary to ensure compliance with quality standards and the sustainability of its use. This study aims to analyze water quality spatially along the Kaludan Polder DIR network and determine water quality status based on the quality standards stipulated in Government Regulation of the Republic of Indonesia Number 22 of 2021. The methods used include sampling at six points representing the estuary, midstream, and outlet sections of the irrigation network, as well as laboratory analysis of 12 physical and chemical parameters: TSS, TDS, pH, DO, BOD, COD, nitrate, nitrite, iron, cadmium, manganese, and copper. Water quality status was further determined using the Storet method and the Pollution Index. The results showed that TSS and COD values in the estuary and midstream sections still exceeded quality standards and were classified as lightly polluted, while at the outlet section, all parameters met quality standards. This pattern indicates that the Kaludan Polder DIR system functions as a natural purification system through sedimentation and degradation of organic matter. Overall, the water quality in the Kaludan Polder DIR remains suitable for use as an irrigation water source with sustainable management.